Impact of COVID-19 on Small and Medium Scale Enterprises Performance: Evidence from Nigeria (International Journal of Management and Sustainability, 2022)
This study assessed the impact of the Covid-19 pandemic on the performance of small and medium scale enterprises (SMEs) in Nigeria using the quasi-experimental research design. Specifically, the study was designed to address three (3) key concerns - how the Covid-19 pandemic impacted on the level of profitability, customers’ patronage and product supply shortages using SMEs owners and hired managers in Warri, Asaba and Ughelli metropolis in Delta State of Nigeria. To do this, a questionnaire was sent to one hundred and thirty (130) respondents and data obtained were analyzed by means of both descriptive (simple percentage, mean, median, standard deviation, variance, skewness and correlation) and inferential (regression and variance inflation factor – VIF) statistical techniques. The findings of the study indicated thattheCovid-19 pandemic negatively and significantly affected the level of profitability, customers’ patronage levels and product supply shortages of SMEs in Delta State of Nigeria. On the basis of the findings, it is recommended, among other things, that the Nigerian government should provide more funds for SMEs; such funds are required to cushion the negative impacttheCovid-19 pandemic imposes on SMEs level of profitability, customers’ patronage and product supply shortages. Again, the government and regulatory agencies of SMEs should gear efforts towards organizing seminars on how businesses can be carried out in a pandemic; this would further pave the way for enhancing SMEs operators’ knowledge on how businesses can be carried out when a pandemic surfaces now or in the future.